Rapid Action of Retinoic Acid on the Hypothalamic Pituitary Adrenal Axis - Imoesi, Peter I.; Bowman, Ellen E.; Stoney, Patrick N.; Matz, Sylwia; McCaffery, Peter (Frontiers in Molecular Neuroscience, 2019)
Retinoic acid is the active metabolite of vitamin A but is also used as a medication, primarily for acne in which the treatment regime lasts several months. A number of studies have indicated that treatment with retinoic acid over this time period impacts the hypothalamic-pituitary-adrenal (HPA) axis and may contribute to a number of the side-effects of the drug. No studies though have investigated the short-term, early effects retinoic acid may have on the HPA axis via the transcriptional pathways activated by the retinoic acid receptor. This study investigated the action of retinoic acid over 3 days on regulatory components of the HPA axis. Several key genes involved in glucocorticoid feedback pathways in the hippocampus, hypothalamus and pituitary were unchanged after 3-days exposure to retinoic acid. Key elements though in the adrenal gland involved in corticosterone and aldosterone synthesis were altered in particular with the Cyp11b2 gene downregulated in-vivo and ex-vivo. The rapid, 5 hours, change in Cyp11b2 expression suggested this activation may be direct. These results highlight the adrenal gland as a target of short-term action of retinoic acid and potentially a trigger component in the mechanisms by which the long-term adverse effects of retinoic acid treatment occur.